2019
DOI: 10.1177/0145721719879421
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Diabetes Self-Management Through Technology and Nurse Health Coaching

Abstract: Purpose This research explores the impact of mobile health (mHealth) technology and nurse health coaching on views of diabetes self-management (DSM) for persons living with diabetes. Methods Three focus groups (N = 24) were conducted with individuals living with type 2 diabetes who participated in a nurse health coaching and mHealth technology intervention study. Qualitative thematic analysis was used to identify overarching themes in each group. Results Major themes identified following intervention participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
(42 reference statements)
0
13
0
2
Order By: Relevance
“…Health coaching may effectively strengthen communication between doctors and patients, and at the same time strengthen sociopsychological support (32,33). Of course, it may also help patients reduce unnecessary or excessive risk perception, strengthen their sense of responsibility of self-management, and encourage patients to regular visit the hospital for normal followups to track diabetes and maintain appropriate healthy living habits according to the recommendations of the doctor (34,35). Because of the lockdown and preventive measures, people's lifestyle and daily habits have changed.…”
Section: Discussionmentioning
confidence: 99%
“…Health coaching may effectively strengthen communication between doctors and patients, and at the same time strengthen sociopsychological support (32,33). Of course, it may also help patients reduce unnecessary or excessive risk perception, strengthen their sense of responsibility of self-management, and encourage patients to regular visit the hospital for normal followups to track diabetes and maintain appropriate healthy living habits according to the recommendations of the doctor (34,35). Because of the lockdown and preventive measures, people's lifestyle and daily habits have changed.…”
Section: Discussionmentioning
confidence: 99%
“…As identified by others (75), patients found virtual care acceptable and accessible, reducing time for travel and lost work (54). People with diabetes particularly liked the safety net provided by virtual monitoring of their health data and some studies reported increased motivation, knowledge of diabetes and uptake of self-care activities (12,48,53,58). However, in one study, patients indicated that face-to-face visits engendered greater motivation (52).…”
Section: Discussionmentioning
confidence: 99%
“…Patient experience: General assessments indicated a high level of satisfaction (32,34,36,38,40,47,54). Emergent themes included increased patient awareness (12,38,53), motivation (12,53) and accountability (39,53); positive behavioural changes (48); and a sense of security that the HCP was regularly monitoring their data (12,18,38,48,54,58) and providing feedback (22). Depending on the devices studied, participants had varying experiences regarding ease of use and reliability (18,46,52,58) and contacting the HCP (22,58), and some found interpreting their own data challenging (18), especially initially (27).…”
Section: Experience Outcomesmentioning
confidence: 99%
“…Quanto ao cargo ou função do enfermeiro que utilizou Coaching, identifica-se em 48% dos artigos (n=16) enfermeiros assistenciais (Sullivan, et al, 2019;Rahn, et al, 2018;Petursdottir, et al, 2019;Hazard, et al, 2018;Berger-Höger, Liethmann, Mühlhauser & Steckelberg, 2017;Early, et al, 2017;Sherry, et al, 2017;Gray-Miceli, et al, 2017;Cooper & Zimmerman, 2016;Janice, Karen, Justine, Sonya & Genevieve, 2015;Bakitas, et al, 2015), 27% (n=8) o enfermeiro pesquisador (Rocha, et al, 2019;Tweedie, et al, 2019;Miyamoto, et al, 2019;Petursdottir, et al, 2019;Berry, et al, 2015), 6% (n=2) de enfermeiros gerentes (Hazard, et al, 2018;, 6% (n=2) de enfermeiros externos (Ouden, et al, 2019;Nyamathi, et al, 2015) e 6% (n=2) enfermeiros de prática avançada Dionne-Odom, et al, 2015), e enfermeiro docente (Ubolrat, et al, 2015) e enfermeiro intervencionista em 3% (n=1) dos artigos.…”
Section: Resultsunclassified
“…Quanto ao tipo de treinamento dos enfermeiros no papel de coach, 36% (n=12) dos artigos não descrevem (Piamjariyakul, et al, 2019;Petty & Lingham, 2019;Noh & Kim, 2019;Petursdottir, et al, 2019;Sherry, et al, 2017;Westland, et al, 2017;Ubolrat, et al, 2015;Berry, et al, 2015;Nyamathi, et al, 2015), 30% (n=10) sinalizam oficinas, workshops, cursos ou treinamentos com textos e vídeos (Tweedie, et al, 2019;Rahn, et al, 2018;Zhang, et al, 2017;Gray-Miceli, et al, 2017;Cooper & Zimmerman, 2016;Janice, et al, 2015;Thoonsen, et al, 2015;Bakitas, et al, 2015;Dionne-Odom, et al, 2015) e 27% (n=9) artigos informa treinamento na ferramenta, técnica ou protocolo aplicado (Sullivan, et al, 2019;Ouden, et al, 2019;Hazard, et al, 2018;Berger-Höger, et al, 2017;Early, et al, 2017; e 6% (n=2) sinalizam formação certificada em Coaching (Rocha, et al, 2019;Miyamoto, et al, 2019).…”
Section: Resultsunclassified